Soil phosphorus fractions dynamics along a 22-ka chronosequence of landslides, western Sichuan, China - He, Junbo; Wu, Yanhong; Zhu, He; Zhou, Jun; Luo, Chaoyi; Bing, Haijian (Catena (Giessen), 2024)
Landslides significant influence on bedrock weathering, pedogenesis, and ecological succession, thereby playing a pivotal role in driving biogeochemical cycles. Landslide chronosequences have traditionally served as invaluable study systems for investigating vegetation succession and exploring soil development and nutrient dynamics. In this study, we analyzed soil phosphorus fractions across a 22,000-year landslide chronosequence. Our investigation examined the impact of environmental factors on these fractions and elucidated the supply of bioavailable phosphorus. Our findings revealed a decline in the concentration of all phosphorus fractions with soil age. Notably, even at an age exceeding 22,000 years, primary mineral phosphorus constituted 23 % of the total phosphorus pool at the later stages of soil development, while organic phosphorus accounted for a mere 7 %. This discrepancy can be attributed to frequent landslides replenishing phosphorus stocks. These findings indicate that the Walker and Syers model may not adequately anticipate alterations in soil phosphorus fractions under geologically unstable landscapes. Environmental factors had limited impact on primary mineral phosphorus concentrations. Yet, they significantly influenced occluded and nonoccluded phosphorus. Changes in organic phosphorus concentrations cannot be fully explained by the examined environmental factors, as organic phosphorus in the soil primarily originates from plant litter decomposition. The sources of bioavailable phosphorus in the investigated region were elucidated using structural equation modeling. The bioavailable phosphorus in the study area is mainly derived from nonoccluded phosphorus rather than organic phosphorus. This observation can be attributed to the distinct landform conditions, which sustain elevated levels of primary mineral phosphorus during soil development. Consequently, the continuous availability of nonoccluded phosphorus ensures a reliable supply of bioavailable phosphorus. In conclusion, the landslide chronosequence serves as a vital example of long-term ecosystem development under unstable landforms. Its refinement of the Walker and Syers model under unstable landscapes.